Highly crystalline bilayer electron transport layer for efficient conjugated polymer solar cells - Xu, C.; Wright, M.; Elumalai, Naveen Kumar; Mahmud, M.; Wang, D.; Upama, M.; Haque, F.; Uddin, A. (Elsevier, 2018)
Solution processed solar cells are a promising renewable energy technology due to the low fabrication costs. The most commonly used electron transport layer for solution processed organic solar cells is ZnO. However, sol-gel derived ZnO is amorphous, which limits interfacial charge transport. In this study, we demonstrate a ZnO bilayer, composed of a nanoparticle ZnO and sol-gel derived ZnO layer, as the electron transport layer in polymer solar cells incorporating the novel polymer poly [(5,6-difluoro-2,1,3-benzothiadiazol-4,7-diyl)-alt-(3,3‴-di (2-octyldodecyl)-2,2′; 5′,2″; 5″,2‴-quaterthiophen-5,5‴-diyl)] (PffBT4T-2OD). Compared with the single layer sol-gel ZnO, the bilayer displayed enhanced crystallinity. Consequently, the interfacial transport from the active layer was improved, as evidenced by dark J-V and PL spectroscopy measurements. Solar cells incorporating this bilayer ZnO layer achieved PCE values exceeding 10%, a relative improvement of 25% compared to the sol-gel ZnO devices.